Honesty in the digital age - Alain Cohn; Tobias Gesche; Michel André Maréchal (University of Zurich, Department of Economics, 2020)
Modern communication technologies enable effcient exchange of information but often sacrifice direct human interaction inherent in more traditional forms of communication. This raises the question of whether the lack of personal interaction induces individuals to exploit informational asymmetries. We conducted two experiments with a total of 848 subjects to examine how human versus machine interaction influences cheating for financial gain. We find that individuals cheat about three times more when they interact with a machine rather than a person, regardless of whether the machine is equipped with human features. When interacting with a human, individuals are particularly reluctant to report unlikely and, therefore, suspicious outcomes, which is consistent with social image concerns. The second experiment shows that dishonest individuals prefer to interact with a machine when facing an opportunity to cheat. Our results suggest that human presence is key to mitigating dishonest behavior and that self-selection into communication channels can be used to screen for dishonest people.
Keywords: C99; D82; D83; 330; Honesty; cheating; human interaction; digitization; social image; screening; Ehrlichkeit; Asymmetrische Information; Betrug; Digitalisierung; Interaktion; Experiment